Gene Expression In Dengue Virus Infection - Wang, Seok Mui. (Universiti Malaysia Sarawak (UNIMAS), 2009)
Dengue virus infection is a major public health problem worldwide and is amongst the most important human disease caused by mosquito-borne viruses. Despite our growing understanding of the various facets of dengue infection, its parthenogenesis still remains elusive.